2020
DOI: 10.1186/s12935-020-1094-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of pretreatment blood lymphocyte count in patients with solid tumors: a systematic review and meta-analysis

Abstract: Background: To evaluate the prognostic value of pretreatment lymphocyte counts with respect to clinical outcomes in patients with solid tumors. Methods: Systematic literature search of electronic databases (Pubmed, Embase and Web of Science) up to May 1, 2018 was carried out by two independent reviewers. We included Eligible studies assessed the prognostic impact of pretreatment lymphocytes and had reported hazard ratios (HR) with 95% confidence intervals (CIs) for endpoints including overall survival (OS) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
82
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 67 publications
4
82
2
Order By: Relevance
“…[4][5][6] Low lymphocyte counts (lymphopenia) may lead to a decrease in immune system's ability to inhibit cancer development, promoting tumor growth and worsening prognosis. 7 OC has an immune-escape mechanism. Malignant cells are associated with immune suppression, enabling cancer cells to evade the host's immune surveillance.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[4][5][6] Low lymphocyte counts (lymphopenia) may lead to a decrease in immune system's ability to inhibit cancer development, promoting tumor growth and worsening prognosis. 7 OC has an immune-escape mechanism. Malignant cells are associated with immune suppression, enabling cancer cells to evade the host's immune surveillance.…”
Section: Introductionmentioning
confidence: 99%
“…Malignant cells are associated with immune suppression, enabling cancer cells to evade the host's immune surveillance. 7,8 The impaired function of the immune system might be directly associated with head and neck squamous cell carcinomas (HNSCC) growth and metastasis. 8 It has also been reported that tumor cells can escape immune surveillance, inhibit immune function, 9 and induce immunogenic cell death and lymphocyte apoptosis, changing lymphocyte homeostasis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neutrophils initiate interactions between cancer cells and endothelial cells in the vicinity of the primary tumor microenvironment to expedite metastasis via the release of growth factors such as vascular endothelial growth factor (VEGF) and proteases [13]. Lymphocytes act to prevent tumor cell proliferation and migration [14]. However, whether alterations in these cell counts result in elevated NLR during NPC progress is controversial [15,16].…”
Section: Introductionmentioning
confidence: 99%